2015
DOI: 10.1002/mawe.201400376
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and fatigue behaviors of polymers for automotive applications

Abstract: An experimental study was conducted on tensile and fatigue behaviors of two unreinforced polymers and two short glass fiber reinforced polymer composites. A number of effects including anisotropy, strain rate and temperature on tensile behavior was investigated. Fatigue behavior was evaluated with respect to effects of mold flow direction, temperature, mean stress, and stress concentration. Effect of mold flow direction on both tensile and fatigue behaviors of unreinforced materials was found to be negligible,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…It can also be observed that the temperature effect is similar for different orientations . Similar stress–strain behaviours has been observed for other SFRPCs at temperatures below and above T g …”
Section: Tensile Behaviourmentioning
confidence: 88%
See 1 more Smart Citation
“…It can also be observed that the temperature effect is similar for different orientations . Similar stress–strain behaviours has been observed for other SFRPCs at temperatures below and above T g …”
Section: Tensile Behaviourmentioning
confidence: 88%
“…Elastic modulus, tensile strength and yield strength decrease almost linearly with increasing temperature for temperatures below and above T g , but with different slopes . Near T g , a drastic reduction in tensile strength and elastic modulus for most of the materials has been observed, an example of which is shown in Fig. for 30 wt% short glass fibre reinforced polybutylene terephthalate (PBT) with T g of about 60 °C .…”
Section: Tensile Behaviourmentioning
confidence: 99%
“…Fatigue life correlation of notched specimens of PBT under fully reversed ( R = −1) condition in the (a) longitudinal and (b) transverse directions, and (c) PP in the transverse direction based on FEA notch root stress, Neuber's rule, and theory of critical distance method.…”
Section: Notch Effectmentioning
confidence: 99%
“…A fatigue life prediction model is also applied to all fatigue data to account for the effects of temperature, fiber orientation angle, and stress ratio. Tensile behaviors of the considered materials were characterized and modeled through conducting tensile tests in a range of temperatures and strain rates on samples prepared in several mold flow directions in [28,29]. The effect of moisture on tensile and fatigue behaviors of these materials was also investigated in [30].…”
Section: Introductionmentioning
confidence: 99%